Understanding Green Purchasing Behavior Through Environmental Attitude: An Empirical Study on Innisfree Consumers - Alfonsius Alfonsius; Gilbert Gilbert (ADI Publisher, 2021)
Lately, consumers are increasingly aware of their purchase behaviors in modern times. They are cognizant of the fact that their consumption habits may have a detrimental effect on environmental sustainability. Marketers have made numerous efforts to develop environmentally friendly products for their customers. This, however, results in a boomerang effect, where customers develop a negative attitude towards the process and label it as greenwashing. Aimed to fill in the knowledge and research object gaps regarding this issue, specifically in Medan, this research assessed how environmental attitude toward green purchasing behavior is influenced by numerous antecedents, including interpersonal influence, altruism, and environmental knowledge. Structural Equation Modelling analysis is employed to assess the relationship between variables. This research indicates that altruism and environmental knowledge have a positive effect on environmental attitude, and that environmental attitude has a positive effect on green purchasing behavior. However, interpersonal influence has a negative effect on environmental attitudes. This shows that marketers should consider these variables when developing an effective campaign capable of eliciting a positive attitude about the environment among the population.